Peran Peran Pemeriksaan Transthorachic Echocardiography Pada Evaluasi Pasien Post Coronary Artery Bypass Graft - Kharisma, Nandika Eki; Sirait, Silfi Pauline; Nurhayati (UHAMKA Press, 2025)
Background: Coronary artery bypass surgery (CABG) is a surgical procedure that aims to restore blood flow to the myocardium that is experiencing blockage or atherosclerosis. After CABG the patient may experience bleeding, pain, infection from the surgical wound, and peri-operative infarction which results in decreased heart function. Thus, examination of the patient is necessary to evaluate the success rate and complications of the CABG procedure. Methods: Literature Review. Analysis: evaluation in patients after CABG surgery was performed by transthoracic echocardiography (TTE) using 2D and motion mode modalities. Both can produce values from left ventricular ejection fraction, wall motion, dimensions of the cardiac chambers as well as hemodynamic assessments TTE examination also aims to determine the presence or absence of side effects from the operation (pericardial effusion, low cardiac output). Conclusion: TTE examination in patients after CABG surgery aims to determine the success rate of surgery, especially to determine whether there are significant changes in heart function (left ventricular ejection fraction, regional wall motion, dimensions of heart chambers, and cardiac output).